Pertimbangan Hukum Hakim terhadap Pertanggungjawaban Perdata Perusahaan Asuransi atas Penolakan Klaim Asuransi Jiwa yang Tidak Beralasan: Studi Putusan Nomor 269/Pdt.G/2023/Pn Mdn - Heidie Nolle Siregar; Tahasak Sahay; Vicka Prama Wulandari; Syamhudian Noor (Jurnal Hukum Lex Generalis, 2026)
Life insurance constitutes a civil agreement creating a reciprocal legal relationship between the insured and the insurer based on the principle of good faith. In practice, disputes frequently arise from claim rejections by insurance companies without clear legal grounds. This study examines the civil liability of insurers for unjustified claim rejections and examines the forms of civil liability imposed on insurers. A normative juridical method is applied using statutory and case approaches, focusing on Decision of the Medan District Court Number 269/Pdt.G/2023/PN Mdn. The findings indicate that groundless claim rejection constitutes breach of contract as unlawful act therein. This study recommends that insurance companies enhance transparency and consistency in policy provisions to prevent disputes in the future.